Biallelic BUB1 mutations cause microcephaly, developmental delay, and variable effects on cohesion and chromosome segregation - Carvalhal, Sara (2022)
Budding uninhibited by benzimidazoles (BUB1) contributes to multiple mitotic processes. Here, we describe the first two patients with biallelic BUB1 germline mutations, who both display microcephaly, intellectual disability, and several patient-specific features. The identified mutations cause variable degrees of reduced total protein level and kinase activity, leading to distinct mitotic defects. Both patients' cells show prolonged mitosis duration, chromosome segregation errors, and an overall functional spindle assembly checkpoint. However, while BUB1 levels mostly affect BUBR1 kinetochore recruitment, impaired kinase activity prohibits centromeric recruitment of Aurora B, SGO1, and TOP2A, correlating with anaphase bridges, aneuploidy, and defective sister chromatid cohesion. We do not observe accelerated cohesion fatigue. We hypothesize that unresolved DNA catenanes increase cohesion strength, with concomitant increase in anaphase bridges. In conclusion, BUB1 mutations cause a neurodevelopmental disorder, with clinical and cellular phenotypes that partially resemble previously described syndromes, including autosomal recessive primary microcephaly, mosaic variegated aneuploidy, and cohesinopathies.